Diaphragmatic and intercostal electromyographic activity during neostigmine, sugammadex and neostigmine–sugammadex-enhanced recovery after neuromuscular blockade: A randomised controlled volunteer study. Issue 1 (January 2017) - Cammu, Guy; Schepens, Tom; De Neve, Nikolaas; Wildemeersch, Davina; Foubert, Luc; Jorens, Philippe G.
Abstract : BACKGROUND: Electromyographic activity of the diaphragm (EMGdi) during weaning from mechanical ventilation is increased after sugammadex compared with neostigmine. OBJECTIVE: To determine the effect of neostigmine on EMGdi and surface EMG (sEMG) of the intercostal muscles during antagonism of rocuronium block with neostigmine, sugammadex and neostigmine followed by sugammadex. DESIGN: Randomised, controlled, double-blind study. SETTING: Intensive care research unit. PARTICIPANTS: Eighteen male volunteers. INTERVENTIONS: A transoesophageal EMGdi recorder was inserted into three groups of six anaesthetised study participants, and sEMG was recorded on their intercostal muscles. To reverse rocuronium, volunteers received 50 μg kg −1 neostigmine, 2 mg kg −1 sugammadex or 50 μg kg −1 neostigmine, followed 3 min later by 2 mg kg −1 sugammadex. MAIN OUTCOME MEASURES: We examined the EMGdi and sEMG at the intercostal muscles during recovery enhanced by neostigmine or sugammadex or neostigmine–sugammadex as primary outcomes. Secondary objectives were the tidal volume, PaO2 recorded between the onset of spontaneous breathing and extubation of the trachea and SpO2 during and after anaesthesia. RESULTS: During weaning, median peak EMGdi was 0.76 (95% confidence interval: 1.20 to 1.80) μV in the neostigmine group, 1.00 (1.23 to 1.82) μV in the sugammadex group and 0.70 (0.91 to 1.21) μV in the neostigmine–sugammadex group ( P < 0.0001 with EMGdi increased after sugammadex vs. neostigmine and neostigmine–sugammadex). The median peak intercostal sEMG for the neostigmine group was 0.39 (0.65 to 0.93) μV vs. 0.77 (1.15 to 1.51) μV in the sugammadex group and 0.82 (1.28 to 2.38) μV in the neostigmine–sugammadex group ( P < 0.0001 with sEMG higher after sugammadex and after neostigmine–sugammadex vs. neostigmine). CONCLUSION: EMGdi and sEMG on the intercostal muscles were increased after sugammadex alone compared with neostigmine. Adding sugammadex after neostigmine reduced the EMGdi compared with sugammadex alone. Unlike the diaphragm, intercostal EMG was preserved with neostigmine followed by sugammadex. TRIAL REGISTRATION: EudraCT: 2015-001278-16; ClinicalTrials.gov: NCT02403063.